Effects of molybdenum to growth parameters and lipid content of two algae in Scenedesmaceae taxa - Celal Caner; Dilara Erdaği; Büşranur Şeker; Hüseyin Altundağ; Gizem Çeti̇n; Hatice Tunca (Heliyon)
Molybdate, an oxidized form of molybdenum, facilitates molybdenum to be taken into cell, and thus to be included as a cofactor in the structure of enzymes necessary to ensure homeostasis. Although this compound provides the catalysis and electron transport of many biochemical reactions, it causes serious health problems in animals at high concentrations. For this reason, its recovery of water resources is one of the main subjects of scientific studies called bioremediaiton. One of the advantages of the remediation is that the biomass obtained from algae increases the amount of lipids, which are the raw material source for the biofuel production. For this purpose, the bioremediation abilities of Desmodesmus pannonicus and Scenedesmus aldavei algae were spectrophotometrically evaluated by using growth rate, chlorophyll-a, chlorophyll-b and total carotenoids for fourteen days. The bioremediation properties were also determined using Inductively coupled plasma - optical emission spectrometry (ICP-OES) analysis. D. pannonicus and S. aldavei algae have bioremediation capabilities up to 1 mg mL−1 Na2MoO4 concentration. The lipid content increased at all concentrations in S. aldavei and at 200 μg mL−1 in D. pannonicus. However, the Mo (VI) contents in dry mass changed depending on the increase of concentrations. Fourier Transform InfraRed Spectrometer analysis (FT-IR) was utilized to identify the alterations of specific functional groups such as carboxyl, amine, hydroxyl, and carbonyl in the samples. As a result, D. pannonicus and S. aldavei have great potential for Mo(VI) bioremediation. D. pannonicus and S. aldavei can tolerate Na2MoO4 up to 1 mg mL−1 concentrations and the lipid content used in biofuel production was increased during this process.